The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15124079
|View full text |Cite
|
Sign up to set email alerts
|

The Gd2−xMgxZr2O7−x/2 Solid Solution: Ionic Conductivity and Chemical Stability in the Melt of LiCl-Li2O

Abstract: Materials with pyrochlore structure A2B2O7 have attracted considerable attention owing to their various applications as catalysts, sensors, electrolytes, electrodes, and magnets due to the unique crystal structure and thermal stability. At the same time, the possibility of using such materials for electrochemical applications in salt melts has not been studied. This paper presents the new results of obtaining high-density Mg2+-doped ceramics based on Gd2Zr2O7 with pyrochlore structure and comprehensive investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…A small effect of pO 2 on the conductivity is seen at all temperatures studied. Analogous dependencies can be found in the literature for Gd 2−x M x Zr 2 O 7−δ (M = Li, Mg) systems [8,9]. Taken into account the specifics of disorder in the studied pyrochlore-like [46] data are also given.…”
Section: Total Conductivity and Defects Equilibriumsupporting
confidence: 75%
See 1 more Smart Citation
“…A small effect of pO 2 on the conductivity is seen at all temperatures studied. Analogous dependencies can be found in the literature for Gd 2−x M x Zr 2 O 7−δ (M = Li, Mg) systems [8,9]. Taken into account the specifics of disorder in the studied pyrochlore-like [46] data are also given.…”
Section: Total Conductivity and Defects Equilibriumsupporting
confidence: 75%
“…Due to their good thermomechanical characteristics, compositions such as Gd 2 Zr 2 O 7 , and (La 1−x Gd x ) 2 Zr 2 O 7 are recommended as thermal barrier coating materials [1][2][3][4][5][6], which is one of the promising applications of pyrochlores. Having high chemical stability, pyrochlores are used as electrolytes for oxygen sensors for aggressive environments, such as Li-based melts [7][8][9]. High radiation resistance allows pyrochlores to be used as materials for the encapsulation of nuclear waste [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of magnesium is accompanied by an increase in the degree of order of 0.95Gd 2 Zr 2 O 7 -0.05MgO by 11.4% compared to the undoped sample. In our previous work [31], it was shown that the intro-duction of magnesium into the structure could be achieved at an amount of 0.05 wt.%, and the calculations were conducted using the Rietveld method. The calculations performed for the two different models of 0.95Gd 2 Zr 2 O 7 -0.05MgO sample presented in Tables 1 and 2 show close results regarding the obtained calculation errors.…”
Section: X-ray Analysis and Sem Characterizationmentioning
confidence: 99%
“…It has been established [31] that the homogeneous magnesium doping of Gd 2 Zr 2 O 7 (solid-solution Gd 2-x Mg x Zr 2 O 7-x/2 ) can prevent the ion exchange of high-density ceramics with LiCl-xLi 2 O melts up to a Li 2 O concentration of 4 wt.%. Thus, a small concentration of magnesium is assumed to be able to protect the material from interaction with the melt [32].…”
Section: Introductionmentioning
confidence: 99%